Nanangenines: drimane sesquiterpenoids as the dominant metabolite cohort of a novel Australian fungus, Aspergillus nanangensis - Lacey, Heather J.; Gilchrist, Cameron L. M.; Crombie, Andrew; Kalaitzis, John A.; Vuong, Daniel; Rutledge, Peter J.; Turner, Peter; Pitt, John I.; Lacey, Ernest; Chooi, Yit-Heng; Piggott, Andrew M. (Beilstein Journal of Organic Chemistry, 2019)
Chemical investigation of an undescribed Australian fungus, Aspergillus nanangensis, led to the identification of the nanangenines – a family of seven new and three previously reported drimane sesquiterpenoids. The structures of the nanangenines were elucidated by detailed spectroscopic analysis supported by single crystal X-ray diffraction studies. The compounds were assayed for in vitro activity against bacteria, fungi, mammalian cells and plants. Bioinformatics analysis, including comparative analysis with other acyl drimenol-producing Aspergilli, led to the identification of a putative nanangenine biosynthetic gene cluster that corresponds to the proposed biosynthetic pathway for nanangenines.
Keywords: Aspergillus; biosynthesis; drimane; secondary metabolites; sesquiterpenoid; terpenes

(untitled) - Heddergott, C.; Calvo, A. M.; Latgé, J. P. (Eukaryotic Cell, 2014)

(untitled) - Huang, J.-H.; Lv, J.-M.; Wang, Q.-Z.; Zou, J.; Lu, Y.-J.; Wang, Q.-L.; Chen, D.-N.; Yao, X.-S.; Gao, H.; Hu, D. (Org. Biomol. Chem., 2019)

(untitled) - Liu, X.-H.; Miao, F.-P.; Qiao, M.-F.; Cichewicz, R. H.; Ji, N.-Y. (RSC Adv., 2013)

(untitled) - Felix, S.; Sandjo, L. P.; Opatz, T.; Erkel, G. (Beilstein J. Org. Chem., 2013)

(untitled) - Felix, S.; Sandjo, L. P.; Opatz, T.; Erkel, G. (Bioorg. Med. Chem., 2014)

(untitled) - de Souza, J. J.; Vieira, I. J. C.; Rodrigues-Filho, E.; Braz-Filho, R. (Molecules, 2011)

(untitled) - Cueto, M.; Jensen, P. R.; Fenical, W. (Org. Lett., 2002)

(untitled) - Hensens, O. D.; Zink, D.; Williamson, J. M.; Lotti, V. J.; Chang, R. S. L.; Goetz, M. A. (J. Org. Chem., 1991)

(untitled) - Zhang, D.; Fukuzawa, S.; Satake, M.; Li, X.; Kuranaga, T.; Niitsu, A.; Yoshizawa, K.; Tachibana, K. (Nat. Prod. Commun., 2012)

(untitled) - Afiyatullov, S.; Zhuravleva, O. I.; Antonov, A. S.; Kalinovsky, A. I.; Pivkin, M. V.; Menchinskaya, E. S.; Aminin, D. L. (Nat. Prod. Commun., 2012)

(untitled) - Bai, Z.-Q.; Lin, X.; Wang, J.; Zhou, X.; Liu, J.; Yang, B.; Yang, X.; Liao, S.; Wang, L.; Liu, Y. (Mar. Drugs, 2015)

(untitled) - Liaw, C.-C.; Yang, Y.-L.; Lin, C.-K.; Lee, J.-C.; Liao, W.-Y.; Shen, C.-N.; Sheu, J.-H.; Wu, S.-H. (Org. Lett., 2015)

(untitled) - Liu, Z.; Liu, H.; Chen, Y.; She, Z. (Nat. Prod. Res., 2018)

(untitled) - Qi, C.; Bao, J.; Wang, J.; Zhu, H.; Xue, Y.; Wang, X.; Li, H.; Sun, W.; Gao, W.; Lai, Y.; Chen, J.-G.; Zhang, Y. (Chem. Sci., 2016)

(untitled) - Shaaban, M.; El-Metwally, M. M.; Abdel-Razek, A. A.; Laatsch, H. (Nat. Prod. Res., 2018)

(untitled) - Liu, H.; Edrada-Ebel, R.; Ebel, R.; Wang, Y.; Schulz, B.; Draeger, S.; Müller, W. E. G.; Wray, V.; Lin, W.; Proksch, P. (J. Nat. Prod., 2009)

(untitled) - Kozlovskii, A. G.; Antipova, T. V.; Zhelifonova, V. P.; Baskunov, B. P.; Ivanushkina, N. E.; Kochkina, G. A.; Ozerskaya, S. M. (Microbiology (Moscow, Russ. Fed.), 2017)

(untitled) - Rahbæk, L.; Christophersen, C.; Frisvad, J.; Bengaard, H. S.; Larsen, S.; Rassing, B. R. (J. Nat. Prod., 1997)

(untitled) - Gould, R. O.; Simpson, T. J.; Walkinshaw, M. D. (Tetrahedron Lett., 1981)

(untitled) - Hamasaki, T.; Kuwano, H.; Isono, K.; Hatsuda, Y.; Fukuyama, K.; Tsukihara, T.; Katsube, Y. (Agric. Biol. Chem., 1975)

(untitled) - Shinohara, Y.; Takahashi, S.; Osada, H.; Koyama, Y. (Sci. Rep., 2016)

(untitled) - Fang, W.; Lin, X.; Zhou, X.; Wan, J.; Lu, X.; Yang, B.; Ai, W.; Lin, J.; Zhang, T.; Tu, Z.; Liu, Y. (Med. Chem. Commun., 2014)

(untitled) - Zhuravleva, O. I.; Afiyatullov, S. S.; Denisenko, V. A.; Ermakova, S. P.; Slinkina, N. N.; Dmitrenok, P. S.; Kim, N. Y. (Phytochemistry, 2012)

(untitled) - Jansen, B. J. M.; de Groot, A. (Nat. Prod. Rep., 2004)

(untitled) - Chaudhary, N. K.; Pitt, J. I.; Lacey, E.; Crombie, A.; Vuong, D.; Piggott, A. M.; Karuso, P. (J. Nat. Prod., 2018)

(untitled) - Lacey, H. J.; Vuong, D.; Pitt, J. I.; Lacey, E.; Piggott, A. M. (Aust. J. Chem., 2016)

(untitled) - Li, H.; Gilchrist, C. L. M.; Lacey, H. J.; Crombie, A.; Vuong, D.; Pitt, J. I.; Lacey, E.; Chooi, Y.-H.; Piggott, A. M. (Org. Lett., 2019)

(untitled) - Pitt, J. I.; Lange, L.; Lacey, A. E.; Vuong, D.; Midgley, D. J.; Greenfield, P.; Bradbury, M. I.; Lacey, E.; Busk, P. K.; Pilgaard, B.; Chooi, Y.-H.; Piggott, A. M. (PLoS One, 2017)

(untitled) - Shiono, Y.; Hiramatsu, F.; Murayama, T.; Koseki, T.; Funakoshi, T.; Ueda, K.; Yasuda, H. Z. (Z. Naturforsch., B: J. Chem. Sci., 2007)

(untitled) - Gao, Y.; Honzatko, R. B.; Peters, R. J. (Nat. Prod. Rep., 2012)

(untitled) - Hitchman, T. S.; Schmidt, E. W.; Trail, F.; Rarick, M. D.; Linz, J. E.; Townsend, C. A. (Bioorg. Chem., 2001)

(untitled) - Lin, H.-C.; Chooi, Y.-H.; Dhingra, S.; Xu, W.; Calvo, A. M.; Tang, Y. (J. Am. Chem. Soc., 2013)

(untitled) - Christianson, D. W. (Chem. Rev., 2006)

(untitled) - Nakano, C.; Okamura, T.; Sato, T.; Dairi, T.; Hoshino, T. (Chem. Commun., 2005)

(untitled) - Cao, R.; Zhang, Y.; Mann, F. M.; Huang, C.; Mukkamala, D.; Hudock, M. P.; Mead, M. E.; Prisic, S.; Wang, K.; Lin, F.-Y.; Chang, T.-K.; Peters, R. J.; et al. (Proteins: Struct., Funct., Bioinf., 2010)

(untitled) - Nakano, C.; Hoshino, T. (ChemBioChem, 2009)

(untitled) - Lu, Z.; Wang, Y.; Miao, C.; Liu, P.; Hong, K.; Zhu, W. (J. Nat. Prod., 2009)

(untitled) - Zhou, H.; Zhu, T.; Cai, S.; Gu, Q.; Li, D. (Chem. Pharm. Bull., 2011)

(untitled) - Cohen, E.; Koch, L.; Thu, K. M.; Rahamim, Y.; Aluma, Y.; Ilan, M.; Yarden, O.; Carmeli, S. (Bioorg. Med. Chem., 2011)

(untitled) - Hayes, M. A.; Wrigley, S. K.; Chetland, I. A. N.; Reynolds, E. E.; Ainsworth, A. M.; Renno, D. V.; Latif, M. A.; Cheng, X.-M.; Hupe, D. J.; Charlton, P.; DoHerty, A. M. (J. Antibiot., 1996)

(untitled) - Slack, G. J.; Puniani, E.; Frisvad, J. C.; Samson, R. A.; Miller, J. D. (Mycol. Res., 2009)

(untitled) - Curlevski, N. J. A.; Xu, Z.; Anderson, I. C.; Cairney, J. W. G. (J. Soils Sediments, 2010)

(untitled) - Gao, X.; Xie, X.; Pashkov, I.; Sawaya, M. R.; Laidman, J.; Zhang, W.; Cacho, R.; Yeates, T. O.; Tang, Y. (Chem. Biol., 2009)

(untitled) - Camacho, C.; Coulouris, G.; Avagyan, V.; Ma, N.; Papadopoulos, J.; Bealer, K.; Madden, T. L. (BMC Bioinf., 2009)

(untitled) - Cerqueira, G. C.; Arnaud, M. B.; Inglis, D. O.; Skrzypek, M. S.; Binkley, G.; Simison, M.; Miyasato, S. R.; Binkley, J.; Orvis, J.; Shah, P.; Wymore, F.; Sherlock, G.; et al. (Nucleic Acids Res., 2014)

(untitled) - Kearse, M.; Moir, R.; Wilson, A.; Stones-Havas, S.; Cheung, M.; Sturrock, S.; Buxton, S.; Cooper, A.; Markowitz, S.; Duran, C.; Thierer, T.; Ashton, B.; et al. (Bioinformatics, 2012)

(untitled) - Buchfink, B.; Xie, C.; Huson, D. H. (Nat. Methods, 2015)